2021
DOI: 10.1155/2021/9592693
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cigarette Smoking Cessation in Pakistan: Evidence from Qualitative Analysis

Abstract: Background. With over 25 million tobacco users, Pakistan has one of the largest smoking populations in the world. Tobacco addiction comes with grave health consequences, especially for the poor and marginalized. Objective. This study explores barriers to smoking cessation in marginalized communities of Islamabad and the possibility of their use of Harm Reduction Products (HRPs), primarily e-cigarettes. Methodology. The study has used primary data of 48 respondents from marginalized communities. Several domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It reduces a complicated dataset to a lower dimension, revealing hidden and simpler patterns. The principal components are new variables formed by linearly combining or mixing the original variables [ 7 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces a complicated dataset to a lower dimension, revealing hidden and simpler patterns. The principal components are new variables formed by linearly combining or mixing the original variables [ 7 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge about nicotine replacement therapy (NRT) can best be described as vague. Higher prices of the alternatives to combustible smoking are a major hurdle preventing their use for smoking cessation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty and other social vulnerabilities compromise the access to smoking cessation support. A qualitative study of smokers from marginalized communities reported that higher price of alternatives to combustible tobacco was a major hurdle for smoking cessation among nicotine dependent smokers [ 50 ]. A study from Kerala, India reported the limited availability & unaffordability of tobacco cessation medications within the health system.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies estimated a total of $3.85 billion smoking-attributable economic cost of all health complications in Pakistan (11). While there is substantial data available highlighting existing behaviors of cigarette smokers as well as the execution of tobacco control measures targeting cigarettes, there is very limited information available from developing countries like Pakistan where the landscape of smoked tobacco consumption is evolving, with newer forms of NCSTP gaining popularity among different demographics (12,13). It is therefore critical to understand people's perception towards the NCSTP forms to alleviate its consumption at the grassroot level.…”
Section: Introductionmentioning
confidence: 99%